2014
DOI: 10.1146/annurev-clinpsy-032813-153716
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sleep in Emotional Brain Function

Abstract: Rapidly emerging evidence continues to describe an intimate and causal relationship between sleep and emotional brain function. These findings are mirrored by longstanding clinical observations demonstrating that nearly all mood and anxiety disorders co-occur with one or more sleep abnormalities. This review aims to (1) provide a synthesis of recent findings describing the emotional brain and behavioral benefits triggered by sleep, and conversely, the detrimental impairments following a lack of sleep, (2) outl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
520
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 703 publications
(581 citation statements)
references
References 146 publications
20
520
3
2
Order By: Relevance
“…Studies in healthy participants demonstrate that both REM sleep density and REM sleep duration during the consolidation interval following encoding of emotional and neutral stimuli correlates positively with memory performance for negative but not neutral stimuli (Gilson et al, 2015;Nishida, Pearsall, Buckner, & Walker, 2009;Payne, Chambers, & Kensinger, 2012). These findings support the notion that REM sleep plays a selective role in the consolidation of negative emotional memories (Goldstein & Walker, 2014;Walker & van der Helm, 2009). …”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Studies in healthy participants demonstrate that both REM sleep density and REM sleep duration during the consolidation interval following encoding of emotional and neutral stimuli correlates positively with memory performance for negative but not neutral stimuli (Gilson et al, 2015;Nishida, Pearsall, Buckner, & Walker, 2009;Payne, Chambers, & Kensinger, 2012). These findings support the notion that REM sleep plays a selective role in the consolidation of negative emotional memories (Goldstein & Walker, 2014;Walker & van der Helm, 2009). …”
Section: Introductionsupporting
confidence: 58%
“…However, the majority of studies directly investigating the effect of REM sleep on emotional memory consolidation focus exclusively on comparisons between recognition performance for neutral and negatively salient stimuli (however see : Cairney, Durrant, Power, & Lewis, 2015), ignoring the possibility that REM sleep may also play a role in the consolidation of positive memories. The amygdala is believed to exert its influence on memory consolidation based on its initial activation during the encoding of emotional information (Markovic et al, 2014), which is thought to underlie the emotion-specific consolidation effects of REM sleep (Bennion et al, 2015;Goldstein & Walker, 2014;Walker & van der Helm, 2009). However, as described earlier, in healthy participants the amygdala responds to both positive and negative material (Kensinger & Schacter, 2006;Vrticka et al, 2014).…”
Section: The 'Affect Tagging and Consolidation' (Atac) Modelmentioning
confidence: 99%
“…(2) Hippocampal but not neocortical lesions caused impairment of SWS, while the neuronal activity in SWS increased in hippocampus but not in neocortex [1][2][3]. For the REM sleep, Cai and others reviewed it as tending to disrupt the emotional balance toward depression [1][2][3][4][5], with the REM sleep deprivation cited as therapeutic against depression [1][2][3].…”
Section: Opinionmentioning
confidence: 99%
“…(2) Hippocampal but not neocortical lesions caused impairment of SWS, while the neuronal activity in SWS increased in hippocampus but not in neocortex [1][2][3]. For the REM sleep, Cai and others reviewed it as tending to disrupt the emotional balance toward depression [1][2][3][4][5], with the REM sleep deprivation cited as therapeutic against depression [1][2][3].For the coincident processing and reorganization of memories in sleep [1][2][3], it has been shown that SWS may favor LTD [6,7], whereas emotional memories are processed during REM sleep, as recently reviewed with many experiments [3], consistent with Freudianism.In addition, Cai's theoretical analysis even revealed a new mechanism manifesting Freudian differentiation of conscious and subconscious conflict of memory and emotion in waking and sleep respectively. During waking, the memory traces were inhibited temporarily by the ascending noradrenergic and serotonergic systems [1][2][3], with the vigilant discharge of these systems regulated by limbicreticular coupling [1,2,8].…”
mentioning
confidence: 99%
“…Sleep is known to specifically promote consolidation of emotionally salient memories (for reviews, see Goldstein & Walker, 2014;Payne & Kensinger, 2010 Kensinger (2008), sleep modifies emotional memories by enhancing the negative aspects of the scene (e.g., a damaged car) at the expense of its neutral aspects (e.g., pedestrians on the pavement; see also Cunningham et al, 2014;Payne, Chambers, & Kensinger, 2012;Payne et al, 2015). In view of this overnight memory trade-off, a straightforward prediction is that negative memories should be even more negative once sleep has occurred.…”
Section: Introductionmentioning
confidence: 99%